Histomorphometric analysis of residual alveolar ridge preserved using collagen cell occlusive membrane alone and along with demineralized bone matrix following tooth extraction: A randomized control trial - Subash Chandra Raj; Shiba Shankar Pradhan; Annuroopa Mahapatra; Neelima Katti; Devapratim Mohanty; Rachna Rath; Kaushik Patnaik; Poonam Agrawal (Wolters Kluwer Medknow Publications, 2022)
Context: The changes in the volume and dimensions of the alveolar bone after tooth extraction often lead to challenges in prosthetic rehabilitation of the same necessitating ridge preservation procedures (RPP). Aim: The aim of this randomized clinical trial was to evaluate and compare the dimensional and histomorphometric changes of the sites preserved using the collagen membrane with and without demineralized bone matrix (DMBM). Settings and Design: Interventional, parallel-design, double blinded, randomized controlled trail. Materials and Methods: A randomized controlled trial was designed with 45 participants having at least 2 teeth indicated for were enrolled in this study. The sites were randomly assigned to the control group (RPP using collagen membrane) and the test group (RPP using collagen membrane with DMBM). The clinical parameters assessed were alveolar bone width and alveolar bone height. Histomorphometric analysis was carried out on tissue trephined from the preserved sites to evaluate the percentage of bone and connective tissue (CT %) formed 8 months postRPP. Statistical Analysis Used: Shapiro − Wilk test and paired and unpaired t-test. Results: Horizontal resorption was significantly less in the test group (7.375 ± 1.64). Histomorphometry of these sites revealed a complete absence of residual graft particles, presence of trabecular bone, and a more mineralized matrix (63.256%) as compared to the control sites (46.833%). Conclusions: The use of DMBM along with the collagen membrane for RPP yielded better results both clinically and histomorphometically.